Subjective Measures of Economic Well-Being and the Influence of Income Uncertainty - Johannes Schwarze (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
This paper provides evidence that subjective measures of individual well being can be used to study the impact of income uncertainty from an ex ante point of view. Two different measures of subjective well being are under study: Satisfaction with household income and the income evaluation question as developed by Van Praag. It can be shown that satisfaction with income is more affected by ex ante than by ex post volatility of income. The ordinal version of the Van Praag approach might be biased if income uncertainty is essential. The paper was written in 1994.
Keywords: C23; D12; D81; I31; 330; Income uncertainty; subjective well-being; satisfaction; income evaluation